Susceptibility of Candida albicans to Punica granatum and correlation with cell surface hydrophobicity - Pozzato, Laura Bernardo; da Silva, Rafaela Alves; Saldanha, Luiz Leonardo [UNESP]; Neppelenbroek, Karin Hermana; Dokkedal, Anne Lígia [UNESP]; Lara, Vanessa Soares; Porto, Vinicius Carvalho (My University, 2018)
Punica granatum L. (Lythraceae) is traditionally used to treat various diseases. Due to the resistance of Candida albicans biofilms to conventional treatments, natural products have been extensively studied. The increase of cell surface hydrophobicity (CSH) has been related to an increment in fungal resistance and virulence. This study evaluated the susceptibility and CSH of C. albicans clinical isolate after exposure to P. granatum, in order to establish whether there is correlation between the two properties. P. granatum showed a fungistatic activity (MIC50 – 8 and 12 mg/ml) (MIC90 – 25 mg/ml). Exposure to 4, 8 and 25 mg/ml did not change fungal CSH. Anti-Candida activity of P. granatum was observed for up to 48 h, indicating that the extract possess a therapeutic potential for treatment and prevention of oral infections, such as denture stomatitis. Also, their fungistatic action was associated with maintenance of the cell wall hydrophilicity of the fungus.
Susceptibilidade de Candida albicans à Punica granatum e correlação com a hidrofobicidade de superfície celular
Keywords: Antifungal activity; Biofilms; Denture Stomatitis; Microbial Sensitivity Tests; Punica granatum